2010
DOI: 10.1007/s10388-010-0234-8
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative chemotherapy with weekly docetaxel plus low-dose cisplatin and 5-fluorouracil for stage II/III squamous cell carcinoma of the esophagus

Abstract: Background. Docetaxel is a powerful anticancer agent for esophageal cancer. Preoperative combined chemotherapy with weekly docetaxel plus low-dose cisplatin and 5-fl uorouracil (DFP) followed by surgery is expected to improve the survival of patients with resectable esophageal squamous cell carcinoma. Methods. Clinical stage II/III squamous cell carcinoma patients who received DFP followed by esophagectomy (NAC group, n = 13) were compared retrospectively with patients who received surgery without preoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…There were no patients whose operation was postponed or who had increased operative complications related to chemotherapy, despite the observed severe adverse events after chemotherapy. No severe postoperative complication was observed, and the complication rates were not significantly different from those described in other reports [60% vs. 55.6%, 61.5%] [21,22]. Response rates were higher than other FP-based regimens, and the DCF regimen appeared to be beneficial for patients who had extensive locoregional LN metastases.…”
Section: Discussioncontrasting
confidence: 55%
“…There were no patients whose operation was postponed or who had increased operative complications related to chemotherapy, despite the observed severe adverse events after chemotherapy. No severe postoperative complication was observed, and the complication rates were not significantly different from those described in other reports [60% vs. 55.6%, 61.5%] [21,22]. Response rates were higher than other FP-based regimens, and the DCF regimen appeared to be beneficial for patients who had extensive locoregional LN metastases.…”
Section: Discussioncontrasting
confidence: 55%
“…Cisplatin plus docetaxel, with or without 5-FU, has demonstrated activity in patients with locally advanced EGI or metastatic esophageal SCC [ 52 - 54 ]. A small-sample retrospective study has also showed that preoperative combined CT with docetaxel plus cisplatin and 5-FU followed by surgery provided a high response rate and a favorable survival benefit in patients with resectable esophageal SCC [ 55 ]. In the docetaxel plus cisplatin and 5-FU group, the overall response rate was 92.3%; 30.8% patients had complete response, 61.5% partial response, 7.7% stable disease, and 0 progressive disease.…”
Section: Discussionmentioning
confidence: 99%
“…4). 30) Recently, our data showed that patients with positive EGFR had a poor prognosis without chemotherapy; however, the prognosis had improved with NAC. EGFR is a predictive factor in the patient's prognosis and response to chemotherapy, and HER2 and HER3 also show similar behaviors.…”
Section: New Therapeutic Strategy For Stage II Iii Esophageal Cancermentioning
confidence: 95%